The LuxS/AI-2 Quorum-Sensing System Regulates the Algicidal Activity of Shewanella xiamenensis Lzh-2 - Liu, Jian; Liu, Kaiquan; Zhao, Zhe; Wang, Zheng; Wang, Fengchao; Xin, Yuxiu; Qu, Jie; Song, Feng; Li, Zhenghua (Frontiers in Microbiology, 2022)
Cyanobacterial blooming is an increasing environmental issue all over the world. Algicidal bacteria are potential tools for the control of algal blooms. The algicidal activity in many bacteria exhibits quorum-sensing (QS) dynamics and the regulatory mechanism of this activity in these bacteria is unclear. In this study, combining genomic sequencing and genome editing, we have identified that the primary quorum-sensing system in the isolated algicidal strain Shewanella xiamenensis Lzh-2 is the LuxS/AI-2 signaling pathway. Disruption of the QS system through recombination deletion of the LuxS gene led to a loss of algicides production and algicidal activity. Restoration of the LuxS gene in the deletion mutant compensated the QS system and recovered the algicidal activity. Consequently, we proved that Lzh-2 regulates the algicidal activity through LuxS/AI-2 quorum-sensing system.